2018
DOI: 10.1021/acs.joc.8b02541
|View full text |Cite
|
Sign up to set email alerts
|

Safer Synthesis of (Diacetoxyiodo)arenes Using Sodium Hypochlorite Pentahydrate

Abstract: A practical method for the preparation of (diacetoxyiodo)­arene ArI­(OAc)2 is described. The use of commercially available sodium hypochlorite pentahydrate (NaClO·5H2O) enabled safe, rapid, and inexpensive oxidation of iodoarenes with electron-withdrawing and -donating substituents. The method allows tandem divergent access to synthetically useful organo-λ3-iodanes such as hydroxyl­(tosyloxy)­iodobenzene, iodosylbenzene, iodonium ylide, etc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
22
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 60 publications
0
22
0
Order By: Relevance
“…18 Surprisingly, conventional 13% and 4% aqueous NaClO solution also served as an effective oxidant, but an excess amount of the reagent led to selective formation of the over-oxidized product PhIO2 6a, instead of 1a (entries 12-14). 14,15 In contrast, Ca(ClO)2-3H2O did not work at all in this system, partly because of its poor solubility in MeCN (entry 15). The substitution of CO2 with solid NaHCO3 is potentially attractive in terms of convenience and cost, though the yield of 1a is only moderate (entry 15).…”
Section: Resultsmentioning
confidence: 94%
See 1 more Smart Citation
“…18 Surprisingly, conventional 13% and 4% aqueous NaClO solution also served as an effective oxidant, but an excess amount of the reagent led to selective formation of the over-oxidized product PhIO2 6a, instead of 1a (entries 12-14). 14,15 In contrast, Ca(ClO)2-3H2O did not work at all in this system, partly because of its poor solubility in MeCN (entry 15). The substitution of CO2 with solid NaHCO3 is potentially attractive in terms of convenience and cost, though the yield of 1a is only moderate (entry 15).…”
Section: Resultsmentioning
confidence: 94%
“…We recently reported that NaClO-5H2O serves as an excellent oxidant for the synthesis of (diacetoxyiodo)arene 2 in the presence of acetic acid at room temperature. 14 We also reported that the oxidation of 2-iodobenzoic acid 7 with NaClO-5H2O, leading to the formation of 2-iodoxybenzoic acid (IBX) 8, is accelerated by gaseous CO2. 15,16 Encouraged by these findings, we commenced our study by examining the direct oxidation of iodobenzene (4a) with NaClO-5H2O under a CO2 atmosphere.…”
Section: Resultsmentioning
confidence: 96%
“…Solid NaOCl·5H 2 O, which has been discovered over a century ago, represented a turning point in our search for a suitable reagent, avoiding some of the previously described shortcomings. As of 2013, this reagent is commercially available [63], inexpensive and sufficiently stable and safe for potential applications in mechanochemistry (Figure S1a, Supporting Information File 1) [6467].…”
Section: Resultsmentioning
confidence: 99%
“…Chloro(tributyl)stannane (>97%), and boron trifluoride etherate (>98%) were purchased from TCI Japan and used as received. (Diacetoxyiodo)benzene (98+%) was purchased from FUJIFILM Wako Pure Chemical or prepared according to the literature (Watanabe et al, 2018). Potassium carbonate (>99.5%) was purchased from FUJIFILM Wako Pure Chemical and used as received.…”
Section: Methodsmentioning
confidence: 99%